2012
DOI: 10.1039/c2dt12274j
|View full text |Cite
|
Sign up to set email alerts
|

A novel water soluble ligand bridged cobalt(ii) coordination polymer of 2-oxo-1,2-dihydroquinoline-3-carbaldehyde (isonicotinic) hydrazone: evaluation of the DNA binding, protein interaction, radical scavenging and anticancer activity

Abstract: A novel water soluble ligand-bridged cobalt(II) coordination polymer has been synthesized by reacting the new ligand, 2-oxo-1,2-dihydroquinoline-3-carbaldehyde (isonicotinic) hydrazone (H 2 L) with Co (NO 3 ) 2 •6H 2 O and characterized by spectral, analytical and structural methods. Single crystal X-ray diffraction studies revealed that the Co(II) complex, {[Co(H 2 L)(H 2 O) 2 ](NO 3 ) 2 •3H 2 O} n has a slightly distorted octahedral geometry around the central Co(II) ion; the ligand is coordinated through th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
130
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 348 publications
(132 citation statements)
references
References 75 publications
2
130
0
Order By: Relevance
“…The char residue of Na doped Co(dtc-SB) is ~22%, while in case of I 2 doping this reduces to 17% (Fig. 5) moiety (Raja, Bhuvanesh, & Natarajan, 2012). The third and final mass loss between 490 o C to 780 o C occurs due to decomposition of the organic part of the ligand (Giovagnini et al, 2008).…”
Section: /2 Xy(imentioning
confidence: 99%
“…The char residue of Na doped Co(dtc-SB) is ~22%, while in case of I 2 doping this reduces to 17% (Fig. 5) moiety (Raja, Bhuvanesh, & Natarajan, 2012). The third and final mass loss between 490 o C to 780 o C occurs due to decomposition of the organic part of the ligand (Giovagnini et al, 2008).…”
Section: /2 Xy(imentioning
confidence: 99%
“…The order of the suppression ratio for DPPHc and OHc is complex 1 > complex 2, while for the NO radicals, the scavenging ability is very close to each other. Even though the DPPHc scavenging ability of complexes were lower than the standards, such as butylated hydroxyanisole (BHA) and butylated hydroxytoluene (BHT) studied in references, 16 the ability was excellent for the DPPH and OH radicals when compared to the standards radicals (Table 4). The IC 50 values (Table 4) indicated that the various radical scavenging activities of the complexes are in the order of OHc > DPPHc > NOc.…”
Section: Antioxidant Activitiesmentioning
confidence: 99%
“…Many Ni(II) and Co(II) complexes bearing hydrazone ligands are known to have radical scavenging properties. 15,16,71 The radical scavenging activities of our compounds in a cell free system have been examined with reference to hydroxyl radical (OHc), DPPH radical (DPPHc) and nitric oxide (NOc) radical and their corresponding IC 50 values have been tabulated in Table 4. The inhibitory effect of the hydrazone ligand and complexes on radicals was also depicted in Fig.…”
Section: Antioxidant Activitiesmentioning
confidence: 99%
See 2 more Smart Citations